Media Berbasis Augmented Reality Pada Pembelajaran IPAS Untuk Meningkatkan Berpikir Kritis Siswa Sekolah Dasar - Yunita Sari; Zainal Abidin; Rida Fironika Kusumadewi; Yulina Ismiyanti; Nuhyal Ulia (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research aims to increase the ability of students to think critically using learning media based on Virtual Augmented Reality in learning knowledge in natural and social sciences. Methodology study This quantitative design is pre-experimental and type pretest-posttest for measuring the effectiveness of the use of learning media based on augmented reality. Research sample This is 24 students in Grade IV at Tambakbulusan Elementary School. For evaluating the effectiveness of virtual augmented reality media in increasing critical thinking in science learning. Data analysis includes validity and reliability tests, normality tests, t-tests for comparison of pretest and posttest scores, as well as calculation of gain value for measuring improvement in critical thinking for students after using virtual augmented reality media in science learning. Research results show that Augmented Reality media can increase the ability to think critically in students, with an average score on the pretest of 33.5 and 82.92 on the posttest. The paired t-test produces a mark of 0.86, indicating there is a significant difference between the score before and after media usage. In addition, the gain test results were 0.74 with the category enough effective. Then it can be concluded that learning media based on augmented reality effectively increases the ability to think at a high level for students in elementary school.